Dataset_EI_Bully_Cyber_Dark_Triad_Moral_Disengagement. - Quintana-Orts, Cirenia Luz; Chamizo-Nieto, María Teresa; Mérida-López, Sergio; Rey-Peña, Lourdes; Extremera-Pacheco, Natalio (Universidad de Málaga, 2024)
The current study examined the roles of dark triad traits, general moral disengagement, and facets of emotional intelligence in bullying and cyberbullying behaviors. A sample of 1,146 (580 girls) adolescents (Mage = 14.19; SD = 1.60) from six high schools participated. Hierarchical regression analyses were used to exploratorily analyze the aforementioned factors. The results revealed that psychopathology, Machiavellianism, and moral disengagement were significantly associated with both bullying and cyberbullying behaviors. Even after accounting for those contributors, the regulation of emotion facet was found to explain a significant amount of unique variance in both aggressive phenomena. The findings of the present study suggest that beyond psychopathology, Machiavellianism, and moral disengagement, the regulation of emotion still matters in preventing cyberbullying aggression in both online and virtual contexts. Identifying and targeting a lack of emotion regulation, even in adolescents with a dark personality and morally disengaged profile, may be important for the prevention of bullying and cyberbullying.
Keywords: Acoso moral; Ciberacoso; Adolescentes - Psicología; Psicopatología; Narcisismo; Sadismo; Madurez afectiva; Bullying; Cyberbullying; Emotional intelligence; Dark triad; Moral disengagement; Adolescence